Non-operative management of pneumoperitoneum following cardiopulmonary resuscitation. Issue 5 (18th May 2022) - Johnson, Christopher L; Gomes, Camilla; Cheng, Justin; Lebares, Carter C
Abstract: Spontaneous pneumoperitoneum in a patient with a tracheostomy tube following cardiopulmonary resuscitation is exceedingly rare, with little experimental nor observational data to guide evidence-based management. We present the case of a 75-year-old woman with a tracheostomy tube who developed pneumoperitoneum following CPR. The patient experienced pulseless electrical activity arrest requiring nine rounds of chest compressions to return to spontaneous circulation. Computerized tomography demonstrated pneumothoraces, subcutaneous emphysema and extensive intraperitoneal, extraperitoneal and retroperitoneal free air without evidence of visceral perforation. The patient's abdomen was distended without tenderness, guarding or rebound. She had a white blood cell count mildly elevated from her baseline levels. The management plan of serial abdominal exams without operative intervention was chosen given the absence of clinical and laboratory signs of peritonitis. This case highlights the importance of developing a standardized management algorithm for patients with pneumoperitoneum in the setting of tracheostomy tubes without evidence of perforation.